Remimazolam tosilate in upper gastrointestinal endoscopy: A multicenter, randomized, non‐inferiority, phase III trial - Chen, Shao‐Hui; Yuan, Tang‐Mi; Zhang, Jiao; Bai, Hua; Tian, Ming; Pan, Chu‐Xiong; Bao, Hong‐Guang; Jin, Xiao‐Ju; Ji, Fu‐Hai; Zhong, Tai‐Di; Wang, Qiang; Lv, Jian‐Rui; et al. (Journal of gastroenterology and hepatology, 2021)
Background and Aim Remimazolam tosilate (RT) is a new short‐acting GABA(A) receptor agonist, having potential to be an effective option for procedural sedation. Here, we aimed to compare the efficacy and safety of RT with propofol in patients undergoing upper gastrointestinal endoscopy. Methods This positive‐controlled, non‐inferiority, phase III trial recruited patients at 17 centers, between September 2017 and November 2017. A total of 384 patients scheduled to undergo upper gastrointestinal endoscopy were randomly assigned to receive RT or propofol. Primary endpoint was the success rate of sedation. Adverse events (AEs) were recorded to evaluate safety. Results The success rate of sedation in the RT group was non‐inferior to that in the propofol group (97.34% vs 100.00%; difference in rate −2.66%, 95% CI −4.96 to −0.36, meeting criteria for non‐inferiority). Patients in the RT group had longer time to adequate sedation (P < 0.0001) but shorter time to fully alert (P < 0.0001) than that in the propofol group. The incidences of hypotension (13.04% vs 42.86%, P < 0.0001), treatment‐related hypotension (0.54% vs 5.82%, P < 0.0001), and respiratory depression (1.09% vs 6.88%, P = 0.0064) were significantly lower in the RT group. AEs were reported in 74 (39.15%) patients in the RT group and 114 (60.32%) patients in the propofol group, with significant difference (P < 0.0001). Conclusion This trial established non‐inferior sedation success rate of RT compared with propofol. RT allows faster recovery from sedation compared with propofol. The safety profile is favorable and appears to be superior to propofol, indicating that it was feasible and well tolerated for patients.